Performance Evaluation of Multimode Fiber-Based Optical OFDM Communication System - Fyath, R. S.; Al-mfrji, Alhuda A. (Nahrain University College of Engineering Journal, 2008)
The most significant limitation of data transmission in Multimode Fibers (MMFs) is intermodal dispersion due to the propagation velocity of each of the guided mode is different. This paper addresses this problem by adopting optical Orthogonal Frequency Division Multiplexing (OFDM) scheme to compensate intermodal dispersion and to enhance the bandwidth-distance product of MMF. The optical OFDM scheme adopted here is based on treating the signal fading due to intermodal dispersion in MMFs in a similar manner to that caused by multipath effect in wireless channels. A MATLAB simulink model is developed for the optical OFDM system. Simulation results are reported for 1Gbps link operating with different digital subcarrier modulation schemes to assess the impact of various parameters on system performance. The results indicate clearly that a Bit Error RateBER) of 10-5 can be achieved for a 1Gbps, 1km (10ns-dispersion) link operating with 1550nm, -23.6dBm laser and 16- Quadrature Amplitude Modulation (QAM) subcarrier modulation scheme.